Clinical Nanomaterials: A Safe‐by‐Design Strategy towards Safer Nanomaterials in Nanomedicines (Adv. Mater. 45/2019). Issue 45 (6th November 2019) - Yan, Liang; Zhao, Feng; Wang, Jing; Zu, Yan; Gu, Zhanjun; Zhao, Yuliang
Abstract : In article number 1805391, Zhanjun Gu, Yuliang Zhao, and co‐workers review clinical potential and toxicological mechanisms of the most important nanomaterials, including liposomes, polymeric and biomacromolecular nanomaterials, inorganic nanomaterials, and carbon‐based nanomaterials with a view to avoiding potential adverse effects of emerging nanomedicines. Based on the available information, an overview of the principles in developing "safe‐by‐design" nanomaterials for medical applications is given.